Five new species of the genus Cheumatopsyche (Trichoptera: Hydropsychidae) from the Phetchabun Mountains, Thailand - Thawarorit, Kitiya; Sangpradub, Narumon; Morse, John C. (Zootaxa, 2013)
Five new species of the genus Cheumatopsyche (Trichoptera: Hydropsychidae) from the Phetchabun Mountains, Thai-land, are described and illustrated. The national parks and wildlife sanctuaries in the Phetchabun Mountains are recognized as areas with a high density of endemic species deserving protection. Four new species of Cheumatopsyche (C. recta, C. diversa, C. triangula, and C. tongto) have been found in Phu Khieo Wildlife Sanctuary, Phu Kradueng National Park and Thung Salaeng Luang National Park; a fifth new species (C. cava) has been found in Phu Kradueng National Park. De-scribing hydropsychid species is important not only to study diversity and distribution but also to facilitate eventual de-scriptions of larvae for use in freshwater biomonitoring programs to detect pollution.